Effect of high forage-to-concentrate ratio pasture feeding on the chemical, physical, and sensory properties of semi-hard goat cheese - Andrea Balivo; Piera Iommelli; Alessandro Genovese; Federico Infascelli; Raffaella Tudisco; Anna Antonella Spina; Riccardo Di Novella; Francesco Addeo; Raffaele Sacchi (Food Chemistry Advances)
The study aims to evaluate the impact of a high forage-to-concentrate ratio diet on the chemical, physical and sensory characteristics of goat cheese, comparing outdoor high-biodiversity pasture feeding (P) to indoor hay-based feeding (S). Twenty Saanen goats were randomly assigned to two groups: the P group, fed on mixed-forage pasture, and the S group fed with alfalfa hay, both supplemented with 400 g/head/day of concentrate. Cheese from both groups was produced in duplicate at the beginning and end of the trial and evaluated after 25 days of ripening at 10 °C. While olfactory, gustatory, and colour descriptors showed no significant differences between the cheeses, P cheese exhibited lower hardness (p = 0.001) and higher friability (p = 0.003). Texture profile analysis and instrumental colour measurements supported the findings of the sensory analysis. The P cheese contained higher levels of unsaturated fatty acids, conjugated linoleic acid (CLA) isomers, and total phenolic compounds, while S cheese exhibited higher concentrations of volatile acids, ketones and lactones. Terpene compounds were unique to the P cheese. Our results suggest that pasture-based feeding with a high forage-to-concentrate ratio can enhance the nutritional profile of goat cheese, with only slight alterations to its sensory properties.